A catalytic asymmetric bioorganic route to enantioenriched tetrahydro- and dihydropyranones. - Baker-Glenn, C; Hodnett, N; Reiter, M; Ropp, S; Ancliff, R; Gouverneur, V (2005)
A conceptually novel approach to hetero Diels-Alder adducts of carbonyl compounds is described using as the key steps an antibody-mediated kinetic resolution of hydroxyenones followed by a ring-closure process. Various beta-hydroxyenones proved to be very good substrates for antibodies 84G3- and 93F3-catalyzed retro-aldol reactions, allowing the preparation of highly enantiomerically enriched (up to 99% ee) precursors of pyranones. An attractive feature of this methodology is the possibility to convert these acyclic-enantioenriched beta-hydroxyenones into tetrahydropyranones by a conventional Michael-type addition procedure or into the corresponding dihydropyranones using an alternative palladium-catalyzed oxidative ring closure. For the palladium-mediated cyclization, a biphasic system has been implemented that allows the direct preparation of enantiopure dihydropyranones from the corresponding racemic aldol precursors using a sequential antibody-resolution/palladium-cyclization strategy, without isolation of the intermediate enantioenriched hydroxyenones. This bioorganic route is best applied to the preparation of hetero Diels-Alder adducts otherwise derived from less nucleophilic dienes and unactivated dienophiles.